PENGARUH PERBEDAAN KONSENTRASI KARAGENAN SEBAGAI EDIBLE COATING TERHADAP SIFAT FISIK, KIMIA DAN MIKROBIOLOGI BUAH STROBERI - Devi, Yuni Astika; Handarini, Kejora (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2025)
Edible coating as one of the post-harvest solutions can be applied as it is safely eaten, covers surface scratches, and gives lustre coating to the strawberries. This study aims to determine the effect of different concentrations of carrageenan as edible coating on the physical, chemical, and microbiological properties of strawberries and to identify the best carrageenan concentration treatment as edible coating so it could retain the physical, chemical, and microbiological properties of strawberries. This research employed 1-factor Completely Randomised Design (CRD), consisting of different concentrations of carrageenan into 4 levels: level 1 = no treatment, level 2 = 2%, level 3 = 2.5%, and level 4 = 3%. Testing parameters were shrinking weight, moisture content, total soluble solids, Total Plate Count (TPC), and Yeast Mould Count (YMC). The results of analysis of variance at the 5% level reveal that carrageenan concentration has very significant effect on shrinking weight, moisture content, total soluble solids, Total Plate Count, and Yeast Mould Count. The treatment of 3% carrageenan concentration yields the best results with shrinking weight (5.2%), moisture content (90.46%), total soluble solids (8.2 oBrix), Total Plate Count 5,2log CFU/g (1,6x105 CFU/g), and Yeast Mould Count 4,2log CFU/g (1,6x104 CFU/g).